Teaching Strategies of the 21st Century Skills Adapted to the Local Needs (European Journal of Teaching and Education, 2023)
Evident is that fact that ICTs are at the core of fast-changing economy. However, ICTs in themselves do not create a knowledge-based economy. Innovation starts with people, making human capital within the workforce decisive. Current workplaces require highly skilled workers who not only need excellent technical preparation but also sufficient skills to adapt to the changing requirements. According to Kozma, a concern about developing future workforces endowed with the "21st century" skills resulted in a goal for school reform that was centered on information communication and technology. Yet, in recent years, the global discourse has evolved to include broader concerns about global citizenship and global competence, resulting in a number of frameworks, which define the 21st century skills. Each framework approaches the skills from a variety of perspectives. The research subject is unveiled through a survey investigation, accompanied by a subcategory known as a descriptive case study. The foundational approach of the provided article is rooted in the quantitative research methodology. Ultimately, the outcomes of the executed analysis will function as a novel methodological instrument for the educators within the Department of Foreign Languages at Y University. This article seeks to conduct a comprehensive evaluation of the theories pertaining to 21st century skills, along with existing definitions and methodologies associated with instructing one specific 21st century skill—citizenship. By utilizing the Republic of Armenia as a contextual case study, the article substantiates the notion that the responsibility for integrating the teaching of this skill lies not only with primary and secondary schools, but also extends to tertiary education establishments. The article underscores the argument that the incorporation of certain, if not all, 21st century skills can be accomplished without necessitating extensive curriculum overhauls or substantial transformations. Instead, minor adjustments introduced within the pedagogical process are deemed sufficient for the successful infusion of these skills into the educational discourse. Additionally, the article comprises two comprehensive lesson plans delineating potential pathways for the progression of the "Engaged Citizen/Citizenship" skill within the curriculum.